Place, Edwin B. and Herbert C. Behm, trans. Amadis of Gaul: A Novel of Chivalry of the 14th Century Presumably First Written in Spanish. Books III and IV. Studies in Romance Languages, vol. 11. Lexington: University of Kentucky Press, 2009. 749 pp. - Rafael Beltrán (Tirant)
-